Les determinants economiques de la performance Olympique - Andreff, M.; Andreff, W.; Poupaux, S. (Working Paper Series, Paper No. 08-19, 2008)
The analysis of economic determinants of Olympic performance was for a long time a macroeconomics of the cold war in which the number of medals won by a nation was explained by its endowment with economic and human resources, then its political regime and a host country effect. We adopt a post-cold war view of the Games which provides an additional explanation closer to the Olympic ideals since it takes into account individual athlete performances, culture, and sporting disciplines. Various econometric estimations that translate this renewed view are achieved under the constraint of limited available data, over 1976-2004. In a first specification inspired from the macroeconomic approach by Bernard and Busse (2004), with a more detailed country classification, GDP per capita, population, the political regime and the host country effect determine the number of medals won. A second specification adds a variable that captures cultural differences across various regions in the world, which improves the previous estimation. A third estimation relies on a new individual data base, introduces an economic classification of sports as a dependent variables and enables estimating, for an athlete from a given country, his/her chances of participating to an Olympic final and of winning a medal. Finally, regarding the prediction of the would-be medal wins in Peking 2008, an inertial variable is introduced in the macroeconomic model in order to capture an `Olympic worship` in those nations which are used to win a number of medals, a variable that differentiates them from other participating nations. Another prevision is based on individual data without any inertia.